STUDENTS' RESPONSES TOWARD TEACHER'S ENGLISH ELICITATION IN EFL YOUNG LEARNERS' CLASSROOM - Mellisha, Anita (2013)
The research titled "Students' Responses toward Teacher's English Elicitation in EFL Young Learners' Classroom" is conducted to describe students' responses toward elicitation techniques implemented in EFL young learners' classroom. The research employs qualitative descriptive method and the data are collected through observation and document analysis. The data from observation and document analysis are analyzed and interpreted to answer the research question in narrative form. The findings of the research reveal that the students' responses as proposed by Suherdi (2010), relevant responses, occurred in all of elicitation techniques. It means that the students respond the teacher's English elicitation positively. Moreover, elicitation using definition is the best elicitation technique that is practiced by the teacher since there are no students' responses of no responses and irrelevant responses. Keyword: Students' Responses, Teacher's Elicitation, Young Learners